2020
DOI: 10.1007/s40123-020-00304-3
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Instruments Targeting Meibomian Gland Dysfunction

Abstract: The most prevalent type of meibomian gland dysfunction (MGD), which is obstructive, is the main cause of evaporative dry eye and is characterized by changes in the meibum composition and duct obstruction. Eyelid hygiene has usually been the most common clinical approach. However, alternative therapies for MGD are emerging on the market. Some warming and humidity devices have led to an improvement in the signs and symptoms in MGD patients. Likewise, eyelid massaging and cleaning devices are also beneficial for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 74 publications
1
7
0
1
Order By: Relevance
“…Various devices specifically designed for in-office MGD management able to produce heating, heating plus humidity, or heating and massaging have been developed and are currently available in the market [ 27 ]. The Activa mask employed in this study was recently validated and preliminary data have shown positive short-term effects (30 minutes after the session) on NIBUT, LLT and ocular discomfort symptoms [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various devices specifically designed for in-office MGD management able to produce heating, heating plus humidity, or heating and massaging have been developed and are currently available in the market [ 27 ]. The Activa mask employed in this study was recently validated and preliminary data have shown positive short-term effects (30 minutes after the session) on NIBUT, LLT and ocular discomfort symptoms [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study found that although IPL could activate fibroblasts and immune cells, it might also skew the metabolic pathway of targeted cells toward a glycolytic phenotype, thereby promoting oxidative stress and apoptosis ( 20 ). Such results affect the assessment of the safety and efficacy of IPL and limit its further application ( 21 , 22 ). On the contrary, instant warm compresses are considered to be a conservative measure that was worth promoting with excellent safety although its mechanism is also not well understood ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of MGD treatment is to increase the flow of meibum secretion thus restoring the release of the lipid layer of the tear film [ 4 6 ]. Apart from medications, eyelid hygiene is the main conservative treatment and involves the use of warm compresses for the local application of heat followed by self-administered mechanical massage of the lid margin [ 7 ]. However, it is difficult for the patient to maintain a standardized and reproducible eyelid hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these drawbacks, novel devices specifically designed for in-office MGD management, able to produce (i) heating, (ii) heating plus humidity, or (iii) heating and massaging, are emerging in the market [ 7 ]. Among these, a novel eye mask producing therapeutic heat (42°) and vibration (up to 20 Hz) for 15 minutes has been recently developed (Activa, SBS Sistemi, Turin, Italy).…”
Section: Introductionmentioning
confidence: 99%